Alumni Assistance to Increase Personal Potential Phase II in Efforts to Reduce Stunting Incidents with Toddler Massage - Ririn Indriani; Susanti Pratamaningtyas; Eny Sendra (Indonesian Journal of Society Development, 2023)
Based on data from 2021, it is predicted that graduates from several health care majors will experience saturation by 2024, including midwifery graduates. Midwifery has a large number of graduates but this is not matched by the availability of job opportunities. This means that some graduates are forced to not work or work that is not appropriate to their field. So the Community Service team created a program entitled "Alumni Assistance to Increase Personal Potential Phase II in Efforts to Reduce Stunting Incidents with Toddler Massage" where this program will provide massage practice training to alumni, mothers and health cadres to prevent and treat stunting in toddlers. The results of the training showed that the average pre-test and post-test scores given to 15 health cadres as respondents were as follows: 8 people (53.33%) had moderate pre-test scores (7-8). Meanwhile, there were 7 people (46.67%) with high scores (9-10). The post test scores experienced a significant increase, namely: medium scores decreased by only 3 people (20%), and high scores (9-10) increased by 12 people (80%). Mentoring and training for alumni and health cadres has been proven to be able to increase the knowledge and skills provided